Show that all of the inflection points of $\displaystyle y = \frac{(1+x)}{(1+x^2)}$ lie on one straight line.
To get the inflection points, we set $f''(x) = 0$ and some for the solution, so...
if $\displaystyle y = \frac{(1+x)}{(1+x^2)}$, then
By using Quotient Rule,
$
\begin{equation}
\begin{aligned}
y' &= \frac{(1+x^2)(1) - (1+x)(2x)}{(1+x^2)^2}\\
\\
y' &= \frac{1+x^2 - 2x -2x^2}{(1+x^2)^2}\\
\\
y' &= \frac{-x^2 - 2x + 1}{(1+x^2)^2}
\end{aligned}
\end{equation}
$
Again, by using Quotient Rule as well as Chain Rule
$
\begin{equation}
\begin{aligned}
y '' &= \frac{(1+x^2)^2 (-2x-2) - (-x^2-2x+1) \left( 2(1+x^2)(2x) \right)}{\left[ (1+x^2)^2\right]^2}\\
\\
y'' &= \frac{2(x-1)(x^2+4x+1)}{(1+x^2)^3}
\end{aligned}
\end{equation}
$
when $y'' = 0$
$
\begin{equation}
\begin{aligned}
0 & = \frac{2(x-1)(x^2+4x+1)}{(1+x^2)^3}\\
\\
0 & = 2(x-1)(x^2+4x+1)
\end{aligned}
\end{equation}
$
We have,
$x - 1 = 0$ and $x^2 + 4x + 1 = 0$ (by using Quadratic Formula)
$x = 1 $ and $x = -2 \pm \sqrt{3}$
Let's evaluate $f(x)$ with these inflection points. So,
$
\begin{equation}
\begin{aligned}
\text{when } x & =1 &&& \text{when } x &= -2 + \sqrt{3},\\
\\
y (1) &= \frac{1+1}{1+1^2} = 1 &&& y(-2+\sqrt{3}) &= \frac{1 + (-2+\sqrt{3})}{1 + (-2+\sqrt{3})^2} = \frac{1+\sqrt{3}}{4}\\
\\
\text{when } x &= 2 - \sqrt{3}\\
\\
y (2 - \sqrt{3}) &= \frac{1+ (-2 - \sqrt{3}) }{1 + (-2 - \sqrt{3})^2} = \frac{1-\sqrt{3}}{4}
\end{aligned}
\end{equation}
$
If we get the equation of the line that pass through points (1,1) and $\displaystyle \left(-2+\sqrt{3},\frac{1+\sqrt{3}}{4} \right)$ by using point slope form..
$\displaystyle y- y_1 = \frac{y_2-y_1}{x_2-x_1} (x-x_1)$
$
\begin{equation}
\begin{aligned}
y -1 &= \frac{\frac{1+\sqrt{3}}{4}-1}{-2 + \sqrt{3}-1} (x-1)\\
\\
y &= \frac{1}{4} (x - 1) + 1\\
\\
y &= \frac{x}{4} + \frac{3}{4}
\end{aligned}
\end{equation}
$
If we substitute the point $\displaystyle \left( 2-\sqrt{3}, 1- \frac{\sqrt{3}}{4}\right)$ to the equation of the line.
$
\begin{equation}
\begin{aligned}
1 - \frac{\sqrt{3}}{4} &= \frac{2-\sqrt{3}}{4} + \frac{3}{4}\\
\\
1 - \frac{\sqrt{3}}{4} &= 1 - \frac{\sqrt{3}}{4}
\end{aligned}
\end{equation}
$
Notice that the points $\displaystyle \left( 2-\sqrt{3}, 1- \frac{\sqrt{3}}{4}\right)$ is also a solution of the tangent line. Therefore, we can say that all the inflection points lie on the same line
Wednesday, January 1, 2014
Single Variable Calculus, Chapter 4, 4.3, Section 4.3, Problem 54
Subscribe to:
Post Comments (Atom)
Why is the fact that the Americans are helping the Russians important?
In the late author Tom Clancy’s first novel, The Hunt for Red October, the assistance rendered to the Russians by the United States is impor...
-
The poem contrasts the nighttime, imaginative world of a child with his daytime, prosaic world. In the first stanza, the child, on going to ...
-
There are a plethora of rules that Jonas and the other citizens must follow. Again, page numbers will vary given the edition of the book tha...
-
The given two points of the exponential function are (2,24) and (3,144). To determine the exponential function y=ab^x plug-in the given x an...
-
Robinson Crusoe, written by Daniel Defoe, is a novel. A novel is a genre defined as a long imaginative work of literature written in prose. ...
-
Hello! This expression is already a sum of two numbers, sin(32) and sin(54). Probably you want or express it as a product, or as an expressi...
-
The title of the book refers to its main character, Mersault. Only a very naive reader could consider that the stranger or the foreigner (an...
-
The only example of simile in "The Lottery"—and a particularly weak one at that—is when Mrs. Hutchinson taps Mrs. Delacroix on the...
No comments:
Post a Comment